KLASTERISASI KECENDERUNGAN KONSUMEN TERHADAP PEMILIHAN MENU MAKANAN MENGGUNAKAN K-MEANS PADA D’BESTO CABANG PONDOK BENDA - Karina Wulandari Sukarman; Munawaroh (Journal of Research and Publication Innovation, 2024)
D'Besto is one of the local franchise restaurants in Indonesia that specializes in serving American cuisine such as Kentucky Fried Chicken, burgers, and French fries. Based on the sales data from the D’Besto branch in Pondok Benda, employees are experiencing difficulties in making accurate decisions to understand consumer preferences regarding menu selections. Therefore, research is needed to identify the most favored menu items among consumers, in order to assist employees in predicting food stock levels. To determine the most popular menu items among consumers, Data Mining Clustering techniques and the K-Means Clustering method are employed. The K-Means Clustering method works by calculating the distance of data points to the nearest Centroid and updating the Centroid values until the Centroid points no longer change. The result of this research is to identify the most popular, moderately favored, and less favored menu items among consumers from July to December 2023. This study resulted in 3 Clusters: C2 contains 24 items consisting of 4 menu items, C1 contains 59 items consisting of 8 menu items, and C3 contains 127 items consisting of 23 menu items. This information serves as a basis for determining the appropriate stock levels for the D’Besto branch in Pondok Benda, focusing on purchasing ingredients for the most popular menu items.